1988
DOI: 10.1002/jnr.490200210
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine hydroxylase and serotonin containing cells in embryonic rat rhombencephalon: A whole‐mount immunocytochemical study

Abstract: Rhombencephala from rat embryos were processed as whole-mounts for immunocytochemical detection of monoaminergic cell populations, using antibodies to tyrosine hydroxylase (TH) and serotonin (5-HT). Specific advantages of the whole-mount technique over the classical serial-section method were that even isolated immunoreactive (IR) cells could be detected easily, and three-dimensional relationships could be ascertained without the need for serial reconstruction. Embryos between embryonic days (E) 12 and 16 (the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(45 citation statements)
references
References 22 publications
(41 reference statements)
0
45
0
Order By: Relevance
“…König et al (1988) mapped TH-IR cells along the whole hindbrain length, but without referring to rhombomeres. They found such cells exclusively in the ''lateral hindbrain'' (their terminology).…”
Section: Dorsoventral Origin Of Catecholaminergic Cell Populations Anmentioning
confidence: 98%
See 2 more Smart Citations
“…König et al (1988) mapped TH-IR cells along the whole hindbrain length, but without referring to rhombomeres. They found such cells exclusively in the ''lateral hindbrain'' (their terminology).…”
Section: Dorsoventral Origin Of Catecholaminergic Cell Populations Anmentioning
confidence: 98%
“…Cell groups A1/C1-C3 in the rat were reconstructed by König et al (1988) as a continuous domain across the caudal hindbrain (our r7/r8), reaching possibly the r6/r7 boundary, as in our material. We concluded that only cells related to the solitary nucleus, area postrema, and dorsal column nuclei should be regarded as alar (A2/C2-alar part).…”
Section: Dorsoventral Origin Of Catecholaminergic Cell Populations Anmentioning
confidence: 99%
See 1 more Smart Citation
“…During this period, a dense plexus of GABA-immunoreactive fibers can be visualized in the rat brainstem as early as embryonic day 13 (Lauder et al, 1986), coinciding temporally and spatially with the appearance and differentiation of tyrosine hydroxylase (TH) containing neurons in the same region (Konig et al, 1988). GABA A receptors are heterooligomeric GABA-gated chloride channels constructed from eight classes of subunits exhibiting varying amino acid sequence homologies (α 1-6 , β 1-4 , γ 1-3 , δ, ρ 1,2 , π, ε and θ ) and when combined produce multiple isoforms of GABA A receptors with varying GABA sensitivities and pharmacologies (Bonnert et al, 1999;Olsen and DeLorey 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, these neurotransmitters and neuropeptides may have other effects on development. For example, catecholamines have been suggested to play an organizing and induction role in the development of the nervous system [35,36]. In an experiment with noradrenaline, Commissiong [35] implanted the locus ceruleus into a transected spinal cord of a rat and reported on an extensive sprouting from the injured fibers, thus implying an induction or trophic effect of the catecholamine secreted by the neurons of the locus ceruleus.…”
Section: Resultsmentioning
confidence: 99%